Bioremediation and microbial degradation of benzo[a]pyrene in aquatic environments: a systematic review. Issue 15 (8th December 2022) - Mortazavi Mehrizi, Morteza; Yousefinejad, Saeed; Jafari, Saeed; Baghapour, Mohammad Ali; Karimi, Ali; Mahvi, Amir Hossein; Jahangiri, Mehdi
ABSTRACT: Benzo[a]pyrene (BaP) is found as an important contaminant in water, air and soil. It can be eliminated through biological removal. The present systematic review aimed to identify the most efficient method for biological removal of BaP from aquatic environments. This systematic review was conducted in 2019, using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) Checklist to investigate the biological removal of BaP from aquatic environments. After searching the databases, 270 studies were found. After the screening stages, 43 studies were reviewed completely. The factors affecting the removal efficiency of BaP including temperature, pH and duration of the experiment (in days) were studied. All 43 studies had reported the pH of the studied environment to be 7.68 (1.04). Six studies reported the mean (SD) temperature to be 31.17°C (4.26°C), and 38 studies reported the mean duration of the experiment to be 69.55 days (166.90 days). Finally, 40 studies reported BaP removal efficiency (Min: 3.8%, Max: 98%). Studies showed the various roles of bacteria and fungi in BaP biodegradation in microbial communities with different ecosystems; in addition, most bacterial species has an important role in BaP biodegradation.